Ntellectuals and the Kosovo problem in SFRJ - Anđelković Stefan N. (Baština)
The topic of this paper is the attitude of Serbian and Albanian intellectuals towards the so-called Kosovo issue. The hypothesis is framed in such a way that both Serbian and Albanian intellectuals played a significant role in articulating the Kosovo issue, but their influence was only one of many factors that contributed to the escalation of antagonisms. This means that their influence was limited within the political context, media control, and other external and internal forces that affected Serbian-Albanian relations. The approaches of Serbian and Albanian intellectuals to resolving the Kosovo issue were heterogeneous, based on differing political positions. Similarly, the influence of intellectuals on public opinion was doubly constrained: by media control exerted by the provincial and federal Yugoslav regimes, and by the influence of Enver Hoxha on Albanian intellectuals in Yugoslavia, whose rule significantly shaped their views on Kosovo. In the end, the intellectual reception of the Kosovo problem was, in most cases, neither sufficiently comprehensive nor did it take into account the spontaneous expressions of discontent from Albanians and Serbs in Kosovo. Therefore, in most cases, it "lagged behind the events."